[Rezension von: Dorin, Rowan, No return : Jews, Christian usurers, and the spread of mass expulsion in medieval Europe] - Tartakoff, Paola (A journal of church and state, 2024)
It is well known that Jews were expelled from Western European kingdoms starting in the late thirteenth century. The expulsions of the Jews from England in